Respuesta :

Answer:

Your answer is the first option, (2,-1).

Step-by-step explanation:

All you have to do is plug the (x,y) values into both equations, then solve and see if they're true.

For the first equation, plug x (aka 2) and y (aka -1) into the places they belong.

2x + y = 3 would become 2(2) + (-1) = 3 after putting the values in the right spots.

Solve.

2(2) = 4.

4 + (-1) = 3

3 = 3.

That means that (2,-1) is the solution for the first equation, however it also needs to be true for the second. Do the same thing and plug the values in their designated spots.

y = x - 3 will become -1 = 2 - 3.

2 - 3 = -1.

So you're left with:

-1 = -1, which means again that (2,-1) is also the solution for that equation.

__________________________________________________________

If you have any questions about any of the process here, ask in the comments of this response and I'll help you out.

ACCESS MORE